Undefined laws, professional weakness - Barea Romero, Cristóbal (Avances en Supervisión Educativa, 2014)
After considering the current regional regulations on the organization and functioning of the Inspectorate of Education, some of its risks are established. The full compliance with the constitutional mandate to inspect the functioning of the educational system with current regulations is questioned. We analyze the basics elements of the laws, focuses on the organizational and functional dependence and territorial structure of inspection services. Finally, we conclude that the vagueness of the rules does not contribute to the professional development of inspection. It suggests that is necessary to tackle the progress and advance on the common minimum given by the associations, is needed.
Keywords: inspectorate of education; organization; performance; law